Evaluated reputation-based trust for WSN security - Said Alkalbani, Abdullah; Md Tap, Abu Osman; Mantoro, Teddy (Little Lion Scientific Islamabad Pakistan, 2014)
During the last years, Wireless Sensor Networks (WSNs) and its applications have obtained considerable momentum. However, security and power limits of WSNs are still important matters. Many existing approaches at most concentrate on cryptography to improve data authentication and integrity but this addresses only a part of the security problem without consideration for high energy consumption. Monitoring behavior of node neighbors using reputation and trust models improves the security of WSNs and maximizes the lifetime for it. However, a few of previous studies take into consideration security threats and energy consumption at the same time. Under these issues Modified Reputation-Based Trust model proposed and optimized for security strength. During evaluation of the model with well-known models two security threats (oscillating and collusion) were applied in order to measure the accuracy, scalability, trustworthiness and energy consumption. As a result, the effects of collusion and oscillating on proposed model are minimized and energy consumption for dynamic networks reduced. Also, simulation results show that MRT has better average accuracy and less average path length than other mechanisms, due to the security and energy aware.